Exploration of the weaving activities in Timor Island for mathematics learning - Wara Sabon Dominikus; Patrisius Afrisno Udil; Ofirenty Elyada Nubatonis; Irna K. S. Blegur (Ethnomathematics Journal, 2023)
The inclusion of ethnomathematical perspectives into the mathematics education of indigenous student is often described as being beneficial. Drawing on weaving activities from West Amarasi society in Timor Island, Indonesia, this paper examines the results from the exploration of mathematical concepts that exist and are practiced in this society. This is a descriptive exploratory with ethnographic qualitative approach research. Data were collected in March 2022 through observations, interviews, and documentation. Some indigenous people from Merbaun Village, West Timor, in East Nusa Tenggara Province, Indonesia, were participants in this research. The results showed that there were several ethnomathematics characteristics in the weaving activities of the West Amarasi society: counting, locating, measuring, designing, explaining, the use of implication logic, and estimating. It was also found mathematics concepts and ways of thinking such as the concept of multiplication as repeated addition, parallel of straight lines, geometric shapes, reflection, rotation, sizes and units, and logical implication. This finding can be used as a source of mathematics learning by teachers, researchers or mathematics education practitioners not only those local in West Amarasi but also in other similar places around the world.